Hubungan Pelaksanaan Praktikum dan Keterampilan Proses Sains Terhadap Hasil Belajar Peserta Didik - Nirwana Elsa Putri; Berti Yolida; Darlen Sikumbang (Universitas Lampung, 2019)
This study aims to determine the correlation of practice and science process skills to learning outcomes of class X students SMAN 13 Bandar Lampung in